Halal Tourism Towards Equity Representation of Multicultural Identity and Human Development: A Case of Lombok, Indonesia - Ameylia Puspita Rosa Dyah Ayu Arintyas; Raihan Chaerani Putri Budiman (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2023)
The tourism trend that is currently developing is the halal tourism trend. The trend towards halal tourism appears because the world's Muslim population currently reaches 1.9 billion and represents a relatively large religious population. One country that has also discussed offering halal tourism is Indonesia. With a Muslim population of around 231 million, Indonesia has the world's largest Muslim population. The Indonesian Ministry of Tourism and Creative Economy (Kemenparekraf) is currently focusing on developing halal tourism, emphasising improving services, especially services that serve the great potential of halal tourism (Muslim-friendly). This study focuses on organizing halal tourism in Lombok, a tourist destination in Indonesia that is internationally recognized for organizing halal tourism. In particular, this study discusses the practices of each activity, such as honeymoon packages or trips to certain locations, as well as the provision of prayer rooms, separate toilets for men and women, and halal certification of halal tourism products in Lombok. Then it analyzes the impact of identity and development—multicultural people towards justice. The method used in this study is a qualitative research method using library materials. The study results show that halal tourism plays an important role in the justice process in representing identity in Lombok. Diversity also creates multicultural understanding for tourists, tour operators and the community. This cross-cultural, reflexive and contextual understanding can be used to advance human development, especially by increasing the standard of living and proper education.